Comparison of Intraocular Pressure Lowering Effect of 0.5% Levobunolol and 0.5% Timolol Maleate after Nd: YAG Laser Capsulotomy - Durraiz Rehman, Sumera Nisar, Tahir Mahmood (Pakistan Journal of Ophthalmology, 2008)
Purpose: To evaluate the efficiency of timolol maleate compared to levobunolol, in the prevention of the intra-ocular pressure (IOP) after Nd: YAG laser posterior capsulotomy. Material and Method: This study was conducted on 50 patients in the department of Ophthalmology, Shaikh Zayed Hospital Lahore. The patients were randomly assigned to receive either 0.5% timolol maleate, 1 drop 12 hourly for 5 days after Nd: YAG laser capsulotomy or 0.5% levobunolol, 1 drop 12 hourly after the procedure. Results: There were no statistically significant differences between the two groups regarding the IOP pre-YAG and 2 hours, first day and 7 days after the laser treatment (p values, respectively: 0.077, 0.085, 0.36, and 0.60). Conclusion: The results of this study suggest that 0.5% timolol maleate is as safe and effective as levobunolol in the prevention of the IOP elevation after Nd: YAG laser posterior capsulotomy.